COMPARATIVE COMPETITION LAW IN HEALTHCARE: A REVIEW OF U.S. AND INDONESIAN REGULATORY APPROACHES - Tjandrawinata, Raymond R. (Ridwan Institute, 2025)
The rapid expansion of digital health services and telemedicine introduces new dimensions to competition law enforcement in healthcare. This paper explores strategic recommendations to enhance Indonesia's competition law in healthcare by focusing on strengthening regulatory institutions, improving judicial consistency, fostering private enforcement mechanisms, and developing targeted policies for emerging digital health markets. This study employs a comparative legal analysis approach, integrating qualitative and normative research methods, to examine the effectiveness of existing competition law frameworks governing healthcare in the United States and Indonesia, identifying best practices, challenges, and opportunities for improvement. The findings reveal stark contrasts in competition law enforced between the two countries, particularly in market concentration, regulatory oversight, judicial intervention, and private litigation mechanisms. By adopting a framework that fosters industry sustainability while preventing anti-competitive behavior, Indonesia can create a more competitive, innovative, and accessible healthcare system that benefits both pharmaceutical companies and consumers alike.